The TREAT‐NMD Duchenne Muscular Dystrophy Registries: Conception, Design, and Utilization by Industry and Academia. Issue 11 (26th August 2013) - Bladen, Catherine L.; Rafferty, Karen; Straub, Volker; Monges, Soledad; Moresco, Angélica; Dawkins, Hugh; Roy, Anna; Chamova, Teodora; Guergueltcheva, Velina; Korngut, Lawrence; Campbell, Craig; Dai, Yi; et al.
<x xml:space="preserve">Abstract</x> TREAT‐NMD is a worldwide network for neuromuscular diseases that provides an infrastructure to support the delivery of promising new therapies for patients. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>